(untitled) (Acta Scientiarum. Health Sciences, 2023)
The research has been conducted with the aim of assessing the situations where women who gave birth during the pandemic develop Vulnerable Baby Syndrome and their fear of COVID-19. The research that is descriptive and cross sectional has been performed with 320 mothers who are accessible and accommodate research criteria. Data have been obtained with the Questionnaire that was sent to participants through social media and by using the Fear of COVID-19 Scale (FCV-19S) and Vulnerable Baby Scale (VBS). It is found that the VBS average score (30.54±09.13) is higher than the cutoff score of the scale(27 score). It is indicated that FCV-19S average score of mothers is 18.52±06.90. No meaningful relation is observed when the correlation between the two scales is examined (r=0.08, p=0.15). As a conclusion, it is indicated that FCV-19S and VBS scores of the mothers are high and it is considered that growth and development of babies who are perceived as vulnerable by their mothers during the pandemic may be at risk. According to the outcome of this research, it can be said that high fear of COVID-19 and vulnerable baby syndrome in mothers affect mother and child mental health negatively.